Pre operative use of injection diclofenac versus injection tramadol for pain management of acute appendicitis in emergency department - Giri, Saroj; Chaudhuri, S; Jirel, S; Aryal, BD; Kumar, DR; Gupta, PP (Health Renaissance, 2017)
Background: Acute appendicitis is one of the most common causes of acute abdominal pain presenting in emergency department. Preoperative use of adequate analgesia markedly reduces pain without affecting diagnosis accuracy and furthermore no single analgesia has been used for this purpose. Objective: To determine and compare the efficacy of injection diclofenac and injection tramadol for rapid pain management of acute appendicitis in emergency department. Methods: An experimental clinical trial was done including 50 patients aged _8 years who were clinically diagnosed as acute appendicitis and had not received analgesia prior to examination by the researcher. They were randomly divided into 2 groups: 25 patients (group 1) were given injection diclofenac intramuscularly and 25 patients (group 2) were given injection tramadol intravenously. Comparative analysis was carried out regarding the decrease in pain intensity using visual analogue scale (VAS) score for pain at presentation, at half an hour and at one hour of drug administration. Results: All the patients had VAS score of _5 at presentation without significant difference in the two groups. Half an hour after drug administration, 64% of subjects still had a VAS score of _6 in the first group while only 12% in the second group (p=0.005). At one hour of drug administration, 64% of subjects had a VAS score between 4 and 7 and 36% had score between 0 and 3 in group 1. In contrast to this score, in group 2 only 16% of the subjects scored between 4 and 7 and 84% between 0 and 3 (p=0.001). Conclusion: There was rapid and marked decrease of VAS score or pain in tramadol group as compared to diclofenac group. Hence, we can recommend that injection tramadol intravenous be considered for preoperative use for pain management of acute appendicitis in emergency department. Health Renaissance 2015;13 (1):